2018
DOI: 10.1063/1.5011401
|View full text |Cite
|
Sign up to set email alerts
|

Novel stable structure of Li3PS4 predicted by evolutionary algorithm under high-pressure

Abstract: By combining theoretical predictions and in-situ X-ray diffraction under high pressure, we found a novel stable crystal structure of Li3PS4 under high pressures. At ambient pressure, Li3PS4 shows successive structural transitions from γ-type to β-type and from β-type to α type with increasing temperature, as is well established. In this study, an evolutionary algorithm successfully predicted the γ-type crystal structure at ambient pressure and further predicted a possible stable δ-type crystal structures under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Li3PS4 has been isolated as four known crystalline polymorphs, β, ϒ, α and δ, the last of which being obtained at high pressure (>5 GPa) [8,12,[14][15][16][17][18][19]. ϒ-Li3PS4, which is formed from a solidstate reaction between 75 mol% Li2S and 25 mol% P2S5 at high temperature (500 -900 °C), possesses a poor RT conductivity of around 10 -7 S.cm -1 [8,9,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li3PS4 has been isolated as four known crystalline polymorphs, β, ϒ, α and δ, the last of which being obtained at high pressure (>5 GPa) [8,12,[14][15][16][17][18][19]. ϒ-Li3PS4, which is formed from a solidstate reaction between 75 mol% Li2S and 25 mol% P2S5 at high temperature (500 -900 °C), possesses a poor RT conductivity of around 10 -7 S.cm -1 [8,9,20].…”
Section: Introductionmentioning
confidence: 99%
“…The phase transformations in Li3PS4 are summarized in Figure 1a. Even though ϒ-Li3PS4 is the equilibrium RT phase [14,19,21], different metastable phases can also be stabilized at RT, as summarized in Figure 1b.…”
Section: Introductionmentioning
confidence: 99%
“…30 A fourth δ polymorph (P42 1 c) has also been identified, although it is only obtainable under high pressure and thus transcends current practical operation. 36 While the structures of these various temperature-dependent polymorphs have been relatively well characterized, the underlying atomicscale features that govern the relationship between cation and anion dynamics remain unclear. Previous work on these materials has been largely devoted to the relevance of static structural manipulation, with significant attention given to the effects, rather than the origin, of subsequent correlative events inherent to fast-ion conduction.…”
Section: Introductionmentioning
confidence: 99%
“…These polymorphic alterations see the hexagonal close-packed (HCP)-like close packing arrangement in the γ polymorph become successively distorted through β to α, approaching the more favorable BCC-like framework with regards to conduction . A fourth δ polymorph ( P 2 1 c ) has also been identified, although it is only obtainable under high pressure and thus transcends current practical operation . While the structures of these various temperature-dependent polymorphs have been relatively well characterized, the underlying atomic-scale features that govern the relationship between cation and anion dynamics remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The complexity of Li 3 PS 4 stems from its distinctive polymorphs and diverse short-range structures. Li 3 PS 4 has four different structures: a low-temperature γ-phase, an intermediate-temperature β-phase, a high-temperature α-phase, and a high-pressure δ-phase. , Previous studies have revealed that the Li + -ion conductivity of Li 3 PS 4 is influenced not only by its long-range structures but also by the short-range structures, which often exhibit a strong correlation to the synthesis protocols. For example, β-Li 3 PS 4 and γ-Li 3 PS 4 synthesized through a solid-state approach exhibit conductivities of 9 × 10 –7 S/cm and 2.6 × 10 –7 S/cm, respectively, while a nanoporous β-Li 3 PS 4 synthesized via a solvent-mediated method shows a significantly higher conductivity of 1.6 × 10 –4 S/cm .…”
mentioning
confidence: 99%